Spine function in Cactaceae, a review - Aliscioni, N. L.; Delbón, N.; Gurvich, D. E. (Journal of the Professional Association for Cactus Development, 2021)
Spines are one of the most conspicuous organs of cacti, and are present even in the most basal species of the family. The aim of this review is to analyse the proven functions of spines, the number of species studied, their taxonomical (subfamily) and the geographic origin of studied species. We found a total of 24 studies that analyzed a total of five functions. A total of 39 species (around 2% of total diversity in the family) were studied. The most studied function was thermoregulation, where spines protect the stem from extreme temperatures, followed by antiherbivory defense. Others functions are water collection, dispersion and antiparasitism defense. Most of the studied species belong to the Cactoideae subfamily, ten to Opuntioideae subfamily and only one, to the Pereskioideae. There is also a bias to the study of species from North America, particularly Mexico and USA. The most studied species was Carnegiea gigantea that was the subject of 5 articles. Surprisingly, there are few studies that analyzed species in environmental gradients or that analyzed the effect of spine removal. These results indicate the necessity of further investigation that include species with different spinescence patterns and which rigorously test possible functions.